Reduced pediatric urgent asthma utilization and exacerbations during the COVID‐19 pandemic. Issue 10 (21st July 2021) - Hurst, Jillian H.; Zhao, Congwen; Fitzpatrick, Nicholas S.; Goldstein, Benjamin A.; Lang, Jason E.
Abstract: The COVID‐19 pandemic has had a profound impact on healthcare access and utilization, which could have important implications for children with chronic diseases, including asthma. We sought to evaluate changes in healthcare utilization and outcomes in children with asthma during the COVID‐19 pandemic. We used electronic health records data to evaluate healthcare use and asthma outcomes in 3959 children and adolescents, 5–17 years of age, with a prior diagnosis of asthma who had a history of well‐child visits and encounters within the healthcare system. We assessed all‐cause healthcare encounters and asthma exacerbations in the 12‐months preceding the start of the COVID‐19 pandemic (March 1, 2019–February 29, 2020) and the first 12 months of the pandemic (March 1, 2020–February 28, 2021). All‐cause healthcare encounters decreased significantly during the pandemic compared to the preceding year, including well‐child visits (48.1% during the pandemic vs. 66.6% in the prior year; p  < .01), emergency department visits (9.7% vs. 21.0%; p  < .01), and inpatient admissions (1.6% vs. 2.5%; p  < .01), though there was over a 100‐fold increase in telehealth encounters. Asthma exacerbations that required treatment with systemic steroids also decreased (127 vs. 504 exacerbations; p  < .01). Race/ethnicity was not associated with changes in healthcare utilization or asthma outcomes. The COVID‐19 pandemic corresponded to dramatic shifts in healthcare utilization, including increased telehealth use and improved outcomes among children with asthma. Social distancing measures may have also reduced asthma trigger exposure.